Herpesvirus Encephalitis in a Little Blue Penguin (Eudyptula minor). Issue 4 (July 2020) - Tuxbury, Kathryn A.; Innis, Charles J.; Thaiwong, Tuddow; Wise, Annabel G.; Maes, Roger; Garner, Michael M.; Kiupel, Matti
An 11-day-old little blue penguin ( Eudyptula minor ) died unexpectedly. Prior to hatching, the egg experienced trauma and resultant defects were repaired. The chick hatched without complication and was clinically normal prior to death. Necropsy revealed congested lungs. Histologic examination showed moderate nonsuppurative encephalitis with focally extensive neuronal necrosis and intranuclear inclusions in neurons within necrotic foci. Herpesvirus DNA was detected in brain tissue with a generic herpesvirus polymerase chain reaction. Sanger sequencing demonstrated 100% and 98% sequence homology to sphenicid alphaherpesvirus 1 and penguin herpesvirus 2, respectively. In situ hybridization demonstrated large amounts of herpesvirus nucleic acid in intranuclear inclusions and neuronal nuclei. Combined histology, polymerase chain reaction, Sanger sequencing, and in situ hybridization results were most consistent with herpesviral encephalitis, most likely caused by sphenicid alphaherpesvirus 1. To our knowledge, this is the first report of a herpesvirus infection causing encephalitis in a penguin and the first report of herpesvirus in this species.